2004
DOI: 10.1002/chin.200413065
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Coupling of Alkynylsilanols with Aryl Halides Promoted by Potassium Trimethylsilanolate.

Abstract: Alkynes Alkynes Q 0087Cross-Coupling of Alkynylsilanols with Aryl Halides Promoted by Potassium Trimethylsilanolate. -In the presence of KOTms, PdCl 2 (PPh 3 ) 2 /CuI, aliphatic alkynylsilanols are found to undergo efficient cross-coupling with aryl iodides. They are more reactive than alkynylsilanes and terminal alkynes. However, aromatic as well as silylated alynylsilanols do not undergo cross-coupling under these conditions. -(DENMARK*, S. E.; TYMONKO, S. A.; J. Org. Chem. 68 (2003) 23, 9151-9154; Dep. Chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…90,91 Additionally, the reaction conditions resemble those for the KOTMS-promoted Hiyama−Denmark crosscoupling reaction. 27 Actually, Denmark and Tymonko examined the KOTMS-promoted activation of the alkynyl TMS in the presence of a copper cocatalyst at ambient temperature, 27 and the similar result was observed in our reaction at 45 °C (entry 9). Although our approach employs a copper cocatalyst with thermal assistance to activate the alkynyl TMSs, we believe that the utility of the alkynyl TMSs as the organosilane species is practically straightforward to versatile synthetic approaches.…”
Section: ■ Results and Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…90,91 Additionally, the reaction conditions resemble those for the KOTMS-promoted Hiyama−Denmark crosscoupling reaction. 27 Actually, Denmark and Tymonko examined the KOTMS-promoted activation of the alkynyl TMS in the presence of a copper cocatalyst at ambient temperature, 27 and the similar result was observed in our reaction at 45 °C (entry 9). Although our approach employs a copper cocatalyst with thermal assistance to activate the alkynyl TMSs, we believe that the utility of the alkynyl TMSs as the organosilane species is practically straightforward to versatile synthetic approaches.…”
Section: ■ Results and Discussionsupporting
confidence: 79%
“…88,89 Denmark and Tymonko reported that potassium trimethylsilanolate (KOTMS) efficiently activates the alkynylsilanols in the Hiyama−Denmark cross-coupling reaction (Scheme 1E). 27 Encouraged by the report, we examined KOTMS as the silanolate instead of methanolate in the synthesis of 1 Ant and found that the KOTMS-promoted conditions drastically improved the yield of 1 Ant (75%) (entry 7). The result indicates the kinetic preference of the Sonogashira catalytic cycles under the KOTMS-promoted conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Initial studies revealed that dimethyl(1-heptynyl)silanol 14 is a much more effective coupling partner than 1-heptyne or (1-heptynyl)trimethylsilane under silanolate activation. 25 With 2.0 equiv of KOSiMe 3 , (Ph 3 P) 2 PdCl 2 , and CuI, the cross-coupling reaction of 14 with 4-iodoanisole is complete after 3 h, whereas 1-heptyne or (1-heptynyl)trimethyl silane affords <20% conversion. Clearly, KOSiMe 3 must activate the silanol without cleavage of the Si-C bond, because in situ deprotection would give identical rates for alkynes 14 and 1-heptyne.…”
Section: Kinetic Analysis and Mechanistic Implicationsmentioning
confidence: 99%
“…10 As an organic base, TMSOK was also explored by Procopiou et al 11 to prepare E-alkenes by inducing the elimination of potassium arenesulfinates from alkyl aryl sulfones. More importantly, the Denmark group found that TMSOK greatly promoted the Sonogashira reaction 12 and the Suzuki−Miyaura reaction 13−16 under anhydrous conditions, reducing the reaction time by more than 10 times. The above examples show the considerable potential of TMSOK as a base to promote the homogeneous, anhydrous Suzuki−Miyaura cross-coupling.…”
Section: Introductionmentioning
confidence: 99%